How do you find the derivative of #y=e^(2x^3)#?
By signing up, you agree to our Terms of Service and Privacy Policy
To find the derivative of ( y = e^{2x^3} ), you can use the chain rule. The chain rule states that if ( y = f(g(x)) ), then ( \frac{dy}{dx} = f'(g(x)) \cdot g'(x) ). In this case, ( f(u) = e^u ) and ( g(x) = 2x^3 ).
So, ( f'(u) = e^u ) and ( g'(x) = 6x^2 ).
Applying the chain rule:
[ \frac{dy}{dx} = f'(g(x)) \cdot g'(x) = e^{2x^3} \cdot 6x^2 = 6x^2 e^{2x^3} ]
So, the derivative of ( y = e^{2x^3} ) is ( 6x^2 e^{2x^3} ).
By signing up, you agree to our Terms of Service and Privacy Policy
When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.
When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.
When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.
When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.
- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7